Answer:
Answer D is correct. The two factors (x - 6) and (x - 3) become zero at x = 6 and x = 3, respectively, showing the x-intercepts of this graph. Additionally, we can see that the sign of the leading coefficient of f(x) = (x - 6)(x - 3) is +, which indicates that the curve opens up. This agrees with the given graph.
Explanation:
The two factors (x - 6) and (x - 3) become zero at x = 6 and x = 3, respectively, showing the x-intercepts of this graph. Additionally, we can see that the sign of the leading coefficient of f(x) = (x - 6)(x - 3) is +, which indicates that the curve opens up. This agrees with the given graph. Answer D is correct.